Incidence, profiles and correlates of the Cortisol Awakening Response in high-functioning young males with ASD. (January 2019) - Sharpley, Christopher F.; Bitsika, Vicki; McMillan, Mary E.; Agnew, Linda L.
Highlights: HPA axis CAR was as expected for group data. Individual CAR were dysregulated in over 50% of participants. No significant correlations were found between CAR and anxiety, depression. Chronic stress may induce hyper- and hypo-cortisolism in ASD. Abstract: Background: The Cortisol Awakening Response (CAR) is sometimes dysregulated in young people with Autism Spectrum Disorder (ASD), but previous findings are mostly based upon group mean data and do not report individual responses. In addition, investigation of the correlates of CAR dysregulation has been limited. Methods: To provide insight into the individual profiles and correlates of the CAR in young males with ASD, 32 high-functioning male participants with ASD aged between 9 yr and 18 yr completed several measures of anxiety and mood, and provided saliva samples at waking and 30 min later for calculation of the CAR. Results: Although group mean data showed an expected CAR profile, over half of the participants had a dysregulated CAR. There was a significant interaction between cortisol concentrations at waking and 30 min later and CAR presence/absence, suggestive of the presence of hyper- and hypo-cortisolism. Unlike previous data regarding CAR and mood states in young females with ASD, there were no significant associations between anxiety or depression and CAR dysregulation in this sample of boys with ASD. Conclusions: The use of the CAR in research and clinical settings must be accompanied by an awareness of the likelihood of individual variability.